Pemanfaatan Google Sites Sebagai Media Promosi Digital Dalam Meningkatkan Eksistensi Pencak Silat Walet Puti - Nia Nuraeni; Ratih Yulia Hayuningtyas; Puji Astuti; Anggun Yuli Asih (Pengabdian kepada Masyarakat Bidang Teknologi dan Sistem Informasi (PETISI), 2026)
This community service activity aims to enhance the visibility and attractiveness of Pencak Silat Walet through the use of a Google Sites–based digital profile as a promotional medium. In the digital era, online platforms play an important role in introducing and preserving local culture, including traditional martial arts such as pencak silat. The main problem identified is the limited use of effective and modern promotional media, resulting in low public awareness of Pencak Silat Walet. To address this issue, a digital profile was developed using Google Sites, accompanied by training for members and administrators. The implementation method included needs analysis, content design, website development, and training sessions. The website content consists of organizational profiles, history, activities, documentation, and membership registration information. The results of this activity indicate that the digital profile serves as an effective promotional tool, improves participants’ digital literacy, and increases public interest in Pencak Silat Walet. Therefore, this initiative not only supports promotional activities but also contributes to the preservation of local culture through the use of digital technology